Investigating student exposure to competency-based education - Ryan, Sarah; Cox, Joshua D. (Education Policy Analysis Archives, 2017)
In recent years, most U.S. states have revised policy by providing schools at least some flexibility to move away from the Carnegie unit system, with its focus on credits and “seat time,” toward competency-based policies that link student advancement to mastery of content. Yet, there is little systematically collected information about how competency-based education is implemented, making it difficult to evaluate the impact on student outcomes. Using data from 600 students in grades 9-12 and confirmatory factor analytic techniques, we report initial reliability and validity results from the pilot administration of a survey designed to capture student exposure to elements that have been described as essential to a competency-based, student-centered model for learning and instruction. These elements include mastery-based progression, personalization, flexible assessment, and the development of specific skills and dispositions. Results suggest that the survey offers a way to reliably measure and study variation in the implementation of competency-based education. Importantly, the survey provides a way to capture implementation from the student perspective, leveraging the fact that student reports about their classroom experiences may be a particularly reliable source of information about instructional practice.